A study of using logit model in predicting corporate take-overs in Singapore. - Han, Kwee Juan. (2009)
The area of mergers and acquisitions has always generated substantial interests amongst practitioners and academics. This is especially so in the use of statistical models to predict acquisition targets based on publicly available financial information. The results of these statistical models have been mixed with accuracy ranging from 64% to 90%.